Antonioni and the aesthetics of impurity : remaking the image in the 1960's - Nardelli, Matilde (Edinburgh studies in film and intermediality., 2020)
The book offers a radical rethinking of Michelangelo Antonioni's work. It argues against prevalent understandings of it in terms of both cinematic purity and indebtedness to painting.